Inhibition of low-density lipoprotein receptor degradation with a cyclic peptide that disrupts the homodimerization of IDOL E3 ubiquitin ligase. Issue 27 (26th June 2018) - Leitch, Eilidh K.; Elumalai, Nagarajan; Fridén-Saxin, Maria; Dahl, Göran; Wan, Paul; Clarkson, Paul; Valeur, Eric; Pairaudeau, Garry; Boyd, Helen; Tavassoli, Ali
Abstract : A cyclic peptide IDOL homodimerization inhibitor identified from a genetically encoded SICLOPPS library is active in vitro and in cells. Abstract : Cellular uptake of circulating cholesterol occurs via the low density lipoprotein receptor (LDLR). The E3 ubiquitin ligase IDOL is a mediator of LDLR degradation, with IDOL homodimerization thought to be required for its activity. To probe the possibility of modulating LDLR levels with an inhibitor of IDOL homodimerization, we screened a SICLOPPS library of 3.2 million cyclic peptides for compounds that disrupt this protein–protein interaction. We identified cyclo -CFFLYT as the lead inhibitor, and improved its activity through the incorporation of non-natural amino acids. The activity of the optimized cyclic peptide was assessed in hepatic cells, with a dose-dependent increase in LDLR levels observed in the presence of our IDOL homodimerization inhibitor.